Effects of bathing in bed with warm water on vital signs and oxygen saturation in adult patients attached to mechanical ventilators - Bayu Firmansyah; Mugi Hartoyo; Supadi Supadi; Budiyati Budiyati (Alma Ata University Press, 2023)
Background: Illness and hospitalization generally require modifications in personal hygiene practices. During hospitalization and especially in the Intensive Care Unit (ICU), patients experience situations involving the need for personal hygiene, procedures performed on them due to limitations arising as a result of the ill condition. Bed bathing is an intervention that must be performed in critical patients with the aim of meeting personal hygiene needs in critical patients, but it is necessary to carry out close monitoring and control to avoid side effects, such as hemodynamic status instability. Objectives:: To determine the effect of bathing in bed with warm water on vital signs and oxygen saturation in adult patients attached with mechanical ventilators. Methods:: This study is a quasi-experimental study involving 18 samples determined by total sampling technique based on inclusion criteria: Patients attached to mechanical ventilators, aged 18 years or older, stable in hemodynamics and exclusion criteria: Attached drugs for the heart, patients with head injuries, receiving drug therapy to lower body temperature.Results: The paired t-test results showed an effect between bathing in bed with warm water on systole blood pressure (p = 0.042; p < 0.005), breathing (p = 0.009), and pulse rate (p = 0.025). There was no effect between bathing in bed with warm water on diastole blood pressure (p = 0.063), body temperature (p = 0.862) and oxygen saturation (p = 0.120). Conclusions : Bed bathing affects systolic blood pressure, breathing, pulse rate and has no effect on diastolic blood pressure, body temperature, and oxygen saturation. However, during bathing in bed should always pay attention to changes that occur in vital signs and oxygen saturation.